Cancer control in member countries of Organization of Islamic Cooperation (OIC)—A status report & İstanbul declaration by the first ladies of OIC. (December 2018) - Kutluk, Tezer; Ataş, Erman; Gültekin, Murat; Torode, Julie; Sullivan, Richard
Highlights: Cancer incidence, prevalence and mortality are increasing in OIC region, a major public health concern here and globally. There is a need for targeted and sustained national investment on cancer control. This will only follow promotion and prioritization of cancer control in the health & development agenda by member countries. Capacity building and health systems strengthening for cancer control is essential for preparedness and making progress on reduction of the cancer burden across the region. Abstract: Cancer is a global public health concern with 14 million new cases and 8 million deaths per year. About 52% of new cancer cases and 59% of 8.2 million deaths in the world occur in OIC (Organization of Islamic Cooperation) countries. For many years cancer were not listed among the health priorities around the globe. The increasing rates in terms of both incidence and mortality with associated healthcare and societal costs have forced countries to invest more in cancer control in different ways from prevention to treatment. In this context and following the World Cancer Leaders' Summit 2015 held in Istanbul in November, the first ladies of OIC countries met in Istanbul in April 14th, 2016 upon the invitation by First lady of Turkey, H.E. Mrs. Erdogan, during the OIC summit. The Istanbul declaration aims to draw attention to the cancer control in the OIC countries to demonstrate the high level support for cancer control programs across the region and encourage all governmental and non-governmental stake-holders to take action for further progress in cancer control from prevention to care. This article summarizes the burden of cancer within the region and presents the İstanbul Declaration by OIC Countries.